Spring wheat productivity and grain quality in the crop rotation of the foreststeppe of Western Siberia - L. V. Yushkevich; I. V. Pakhotina; А. G. Shchitov (Зерновое хозяйство России, 2021)
Spring bread wheat is cultivated in the Omsk region, mainly in grain-fallow crop rotations, repeated and perma[1]nent crops, less in crop-changing rotations and occupies up to 73% of the grain share of Western Siberia. Soybean crops are growing in the region, but at the same time, there have not been sufficiently studied the peculiarities of the cultivation technology of spring wheat sown after this forecrop. The purpose of the current study was to establish the efficiency of agricultural cultivation technologies of spring wheat in the crop rotation sown after soybean in the southern forest-steppe of Western Siberia. The study was carried out in a stationary crop rotation with alternating crops (soy[1]beans – spring wheat – oil flax – barley) in the laboratory for resource-saving agricultural technologies of the Omsk Research Center on meadow-blackearth soil in 2011–2019. There has been established that the soil cultivation system and the means of intensification influenced the elements of fertility and the phytosanitary state of the agrophytocenosis of spring wheat sown after soybean. With subsurface plowing, in comparison with moldboard plowing, there was an increase in biomass and number of weeds on 21 and 43%, respectively. The use of chemicals resulted in a significant increase in spring wheat biomass (on 1.8 times) and a decrease in number of weeds (on 3.3 times), which had a noticeable effect on the productivity. Productivity of wheat sown after soybeans decreased with a decrease in tillage intensity from moldboard plowing to subsurface plowing on 16%. The intensive cultivation technology of spring wheat increased its productivity up to 3.32 t / ha, the protein and gluten content in grain on 16–18%. As for chemicals, the maximum grain number increase on 28.2% was provided by the use of fungicides compared to the control (1.46 t/ha).